Salary Satisfaction of Vietnamese Teachers - Hà, Lê Vũ; Thủy, Nguyễn Thanh; Thịnh, Trần Thị (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: The research aims to clarify the salary and satisfaction levels of Vietnamese preschool and high school teachers today.Methodology: Data was collected from 869 teachers and administrators working at preschools, primary schools, lower secondary schools, upper secondary schools, and inter-level schools in both public and private schools across the country through an online survey (questionnaire designed on Google form), combined with online interviews with 13 teachers and administrators. Data were processed using SPSS software version 28.0 to analyze descriptive statistics, One-way analysis of variance (ANOVA), and post-test to detect differences in salary levels and teachers' satisfaction with aspects of being paid.Main Findings: Research results show that there is no difference in the average monthly income of teachers according to training level; the difference in salaries of preschool teachers and high school teachers shows that the current salary mechanism in Vietnam gives more priority to general education; teachers' satisfaction with salary level is only at a normal level; there are differences in teachers' allowances between delta areas, mountainous areas, and remote islands.Novelty/Originality of this study: The study offers some new findings, for example there is no difference in average salary between teachers with different training levels, or salary satisfaction of private school teachers is higher public school teacher. The research also provides helpful information for policymakers about teacher salaries in Vietnam in the coming time, especially in the context of upcoming changes in salary policy from July 1, 2024.